An Examination of How DUI-Child Endangerment Laws Are Used in Court. Issue 7 (July 2021) - Romano, Eduardo; Kelley-Baker, Tara; Taylor, Eileen P.
Each year, about 200 children aged 14 years old (y/o) or less die and another 4, 000 are physically injured while being driven by an adult that has been drinking (aged 21 y/o or more). Concerned by this phenomenon, there are a growing number of States implementing Driving Under the Influence – Child Endangerment (DUI-CE) laws to prevent adults from driving under the influence with children. These laws however, have failed to reduce the rates of DUI-CE injuries and fatalities. It has been hypothesized that such a failure occurs, at least in part, because these laws are being pled-down in courts, this study examines this hypothesis. We analyzed DUI-CE related court information collected by court monitors available in the Court Monitoring Database (CMD) provided by the Mothers Against Drunk Driving (MADD). Despite investigating data that included only DUI offenders who were driving with at least one child passenger at the time of the arrest, only 10% of those charged with a DUI felony and 11% of those charged with a misdemeanor were also found guilty of a DUI-CE violation. These findings support the hypothesis that DUI-CE offenses are being pled down in court and probably contribute to the ineffectiveness of DUI-CE laws. Unfortunately, data limitations preclude any decisive conclusions. Future research should focus on increasing our understanding of the DUI-CE problem and understanding why DUI-CE laws are not working toward the goal of deterring and punishing those who endanger the lives of children.